2023
DOI: 10.3390/ijms24021514
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenolics Profile in Freeze-Dried Apple Peel and Their Bioactivities during In Vitro Digestion and Colonic Fermentation

Abstract: Freeze-dried apple peel powder (Fd-APP) was subjected to in vitro digestion and colonic fermentation to evaluate the variations in its phenolic composition, bioactivities (antioxidant activity, α-amylase, and α-glucosidase inhibition), and fecal metabolic outputs. A total of 88 phenolics were tentatively identified, of which 51 phenolic compounds were quantitated in Fd-APP sample extracts before digestion, and 34 were released during subsequent phases of digestion. Among these, phenolic acids showed the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 63 publications
(98 reference statements)
3
28
0
Order By: Relevance
“…Compounds 83 (quercetin 3-(2-galloylglucoside) and 88 (quercitrin) were only identified in lemon aspen while compounds 80 (6-hydroxykaempferol 3,6-diglucoside 7-glucuronide), 86 (kaempferol 3-rutinoside), 87 (kaempferol 3-O-arabinoside), and 90 (quercetin 3-O-arabinoside) were only identified in mountain pepper berries. Compounds 84 (rutin), 92 (quercetin-3-O-glucoside), 93 (Isorhamnetin), 95 (myricetin), 96 (taxifolin), and 98 (quercetin) were identified through the MS/MS spectra of pure standards [53]. The resulting ions at m/z 300 and 271, which correspond to the loss of CH 3 and CO 2 from the precursor [1,18], were used to identify isorhamnetin (compound 93 at ESI − m/z 315.0504), which was identified in mountain pepper berries, lemon aspen, and strawberry gum.…”
Section: Flavonols Dihydroflavonols and Chalconesmentioning
confidence: 99%
“…Compounds 83 (quercetin 3-(2-galloylglucoside) and 88 (quercitrin) were only identified in lemon aspen while compounds 80 (6-hydroxykaempferol 3,6-diglucoside 7-glucuronide), 86 (kaempferol 3-rutinoside), 87 (kaempferol 3-O-arabinoside), and 90 (quercetin 3-O-arabinoside) were only identified in mountain pepper berries. Compounds 84 (rutin), 92 (quercetin-3-O-glucoside), 93 (Isorhamnetin), 95 (myricetin), 96 (taxifolin), and 98 (quercetin) were identified through the MS/MS spectra of pure standards [53]. The resulting ions at m/z 300 and 271, which correspond to the loss of CH 3 and CO 2 from the precursor [1,18], were used to identify isorhamnetin (compound 93 at ESI − m/z 315.0504), which was identified in mountain pepper berries, lemon aspen, and strawberry gum.…”
Section: Flavonols Dihydroflavonols and Chalconesmentioning
confidence: 99%
“…In addition, many authors have explained the reduction of ( poly)phenols in the gastric phase and then their increase in the intestinal phase because of the pectin jellification that occurred in the gastric phase, which could entrap ( poly)phenols, and then the increase of pH destabilizes the pectin matrix and releases the entrapped ( poly)phenols. 53 On the other hand, the significant differences observed in the bioaccessibility of ( poly)phenols between the six studied plant-based matrices could be mainly related to the different heat treatments underwent by the matrices (convection, flame, and pasteurization), as well as the presence or absence of oil in the food matrix, whereas repercussed in different interactions between the ( poly)phenols-food matrix and ( poly) phenols-bile acid. Eran Nagar et al reported the ( poly) phenols-bile acid interaction as the main factor in reducing the bioaccessibility of ( poly)phenols, higher than the food matrix or pH increase.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, many authors have explained the reduction of (poly)phenols in the gastric phase and then their increase in the intestinal phase because of the pectin jellification that occurred in the gastric phase, which could entrap (poly)phenols, and then the increase of pH destabilizes the pectin matrix and releases the entrapped (poly)phenols. 53…”
Section: Discussionmentioning
confidence: 99%
“…New functional dairy products presenting potential advantages for health are currently in high demand from increasingly health‐conscious consumers (Bulut et al., 2022: Zahid et al., 2023). Among dairy products, yogurt is the most popular fermented milk and an excellent source of protein, calcium, vitamins, lipids, and minerals (Rashwan et al., 2023).…”
Section: Intoductionmentioning
confidence: 99%
“…Several experiments have also been conducted in this respect to produce yogurts supplemented with bioactive compounds from plants, such as rosemary (Ali et al., 2021) and moringa (Zhang et al., 2019) extracts, Chinese sweet tea (Abdel‐Hamid et al., 2020), and mango peel powder (Zahid et al., 2023). The majority of this research has focused specifically on the antioxidant properties of yogurts supplemented with plant extracts, with only a few going so far as to examine the effects of phenolic extracts on lipid acid composition.…”
Section: Intoductionmentioning
confidence: 99%